Feasibility study of air catcher for natural ventilation application - Sarhan, Ali Raheem (2015)
Ventilation is the process of supplying fresh air and removing stale air. Natural ventilation is an effective method to save energy required to condition building and to improve indoor air quality. It is widely recognized as contributing in low energy building design. In present work, five types of low Reynolds number airfoils were used to design air catchers with three angles of attack and four different diameters. SolidWorks was used to build the geometries and Computational Fluid Dynamics (CFD) was used to simulate the buoyancy driven natural ventilation. Mesh dependency test has been done for three sizes of mesh and result was validated by comparing the numerical result with experimental result for NACA2415 airfoil. Sixty cases were studied by considering five types of airfoils air catchers, three angles of attack ( 0°, 10° and 20 °) with four diameters ( 0.75Cax, 1Cax, 2.5Cax and 3Cax ) for each type by using CFX ANSYS with k-ε turbulence model. All the configurations show improvement on the effective mass flow rate. Nominal and effective mass flow rates and improvement factor were calculated for each case. It is observed that the improving factor increased with angle of attack and decreased with diameter. The results showed that the best improvement factor was found at S1223 air catcher with 112.5 mm diameter and 20° angle of attack. Therefore, the air catcher is feasible for the natural ventilation application.